السلطات الإدارية المستقلة في مجال الإعلام و الإتصال في الجزائر - غمام عمارة، محمد الامين (جامعة الوادي University of El Oued, 2024)
تعتبر السلطات الإدارية المستقلة هيئات ذات طبيعة خاصة تساند الدولة من خلال مباشرتها لصلاحيات و اختصاصات هامة في تسيير قطاعات مالية و اقتصادية. و من أجل تحقيقها للأهداف التي أنشئت من أجلها مكنها المشرع من ممارسة سلطة اتخاذ القرارات، و منحها الاستقلال و الشخصية المعنوية، بالإضافة إلى مجموعة من الآليات الفعالة التي تضمن لها مباشرة اختصاصاتها، و من جهة أخرى نجد أن المشرع قد أخضع أعمال هذه الهيئات إلى الرقابة القضائية. و قد أسس المشرع سلطات إدارية مستقلة في مجال الإعلام و الاتصال تهدف إلى تعزيز حرية التعبير و ضمان تنظيم هذا القطاع بشكل فعال و عادل، حيث أنشأ و نظم سلطة الصحافة المكتوبة و الصحافة الإلكترونية بموجب القانون رقم 23-19، و السلطة الوطنية المستقلة لضبط السمعي البصري بموجب القانون رقم 23-20. The independent administrative authorities are specialized bodies that support the state by exercising important powers and competencies in managing financial and economic sectors. In order to achieve their objectives, for which they were established, the legislature has empowered them to exercise decision-making authority, granting them independence and legal personality, in addition to a set of effective mechanisms to ensure the direct exercise of their powers. On the other hand, we find that the legislature has subjected the actions of these authorities to judicial oversight. The legislature has established independent administrative authorities in the field of media and communication aimed at enhancing freedom of expression and ensuring the effective and fair regulation of this sector. This includes the establishment and regulation of the written press and electronic media authority under Law No. 23-19, and the establishment of the independent national authority for audiovisual regulation under Law No. 23-20.
ماستر اداري